STUDI INTERAKSI MOLEKUL KOMPONEN MINYAK NILAM DENGAN RESEPTOR OLFAKTORI SEBAGAI REPELLENT NYAMUK CULEX sp SECARA IN SILICO DAN IN VITRO - Nidianti, Ersalina; Utomo, Edi Priyo; Himawan, Toto (Jurnal Ilmu Kimia Universitas Brawijaya, 2014)
The components of patchouli oil consist of mayor e.g patchouli alcohol and minor component such as patchoulene, α-guaiene, syechellen, and caryophyllene. These compounds are potentially as repellent or attractant against insects. The purpose of this research is to determine the activity of the Culex sp mosquito repellency using patchouli oil in silico and in vitro. Assessment of in silico modeling is through based on interactions of terpenoid  the Culex sp mosquito olfactory receptor structure was downloaded from www.pdb.org with access code 3OGN while the ligand structure downloaded from www.ncbi.nlm.nih.gov. The modeling by using Autodock Tools 1.5.4 docking of the ligands were done in consecutive performing of α-guaine, α-patchoulen, vellence, caryophyllene, and syechellen respectively. In comparing with commercial repellent DEET, the patchouli oil component with minus patchouli alcohol have more potent as repellent with Kd = 330 µM, while Kd of DEET is 7,31 µM. Patchouli oil components have potential as a repellent better than DEET, it is indicated from Kd values greater than Kd DEET.  By in vitro experiment, patchouli oil showed repellency at EC50 = 6,19 ± 0,55 ppm. Keywords: Computational chemistry, Patchouli Oil, Repellent